2015
DOI: 10.1111/ans.13274
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular reconstruction: meta‐analysis of iliac‐ versus fibula‐free flaps

Abstract: Both iliac- and fibula-free flaps should be considered for use in mandibular reconstruction. We suggest the iliac crest as the first choice for mandibular angle or body defects (better contour match) or also defects requiring greater soft-tissue bulk for intra-oral lining. The fibula flap is best when bony length is required such as in subtotal or total mandibulectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 45 publications
(41 reference statements)
3
61
0
6
Order By: Relevance
“…We preferred the use of the vascularized iliac crest flap. There are no significant differences in terms of morbidity of the donor site between iliac crest and fibula free flaps patients [17]. All patients of the present series experienced pain at the donor site, which lasted for a mean time of 1.7 months; nevertheless, a follow-up of more than 6 months showed no residual donor site morbidities.…”
Section: Discussionmentioning
confidence: 49%
“…We preferred the use of the vascularized iliac crest flap. There are no significant differences in terms of morbidity of the donor site between iliac crest and fibula free flaps patients [17]. All patients of the present series experienced pain at the donor site, which lasted for a mean time of 1.7 months; nevertheless, a follow-up of more than 6 months showed no residual donor site morbidities.…”
Section: Discussionmentioning
confidence: 49%
“…However, despite its merits, harvesting and contouring of the fibula demands tremendous skill and expertise. Furthermore, post-operative facial symmetry is an important aesthetic aspect, which is very difficult to achieve (67). Previous studies have reported that harvesting the fibula increases the risk of donor-site morbidity, and lowers walking endurance in the short-term and decrease the ability to do strenuous activity in the long-term (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…All blood samples were consistently processed and managed as described in specific protocols, no tissue biopsies needed to be the retromolar area of the mandible [9]. Based on current insights from clinical human studies, bone grafts from the iliac crest are suitable for the reconstruction of large defects and atrophic edentulous alveolar crests in the mandible and maxilla [10][11][12]. Despite the still widespread use of iliac bone grafts for reconstructive surgery in dentistry, harvestingespecially from the anterior part of the iliac crest-partially leads to a prolonged operating time as well as to major complications and donor site morbidity, including extended healing periods, chronic donor site pain, functional impairment, wound dehiscence, and deep infections [9,[13][14][15][16][17].…”
Section: Study Design and Participantsmentioning
confidence: 99%